Nursing Manager Trainig From Past To Today - Hanife Tiryaki Şen; Burcu Alaçam; Tuğba Öztürk Yıldırım (Association of Nurse Managers, 2019)
No matter which branch of industry and service area; today, it is necessary for administrators to have adequate information about their service area, certain experience on their duties, leadership characteristics in terms of personality traits as well as having been required to acquire appropriate knowledge, skill and attitude in order to overcome their duties in certain organizational situations. For that reason, according to the executive proficiency which the administrators should have, educational programs appropriate for application area and the characteristics of the institution, which can meet the necessities and provide success for them in their current and future jobs, should be prepared. In order for the administrators to fulfil the expected roles of the nurse executives who are responsible for presenting quality nursing services, nurse executive trainings have recently become crucial. In this review, nurse executive training has been analyzed from past to present.